Zollinger-Ellison Syndrome: An Uncommon Cause of Peptic Ulcer Disease and Chronic Diarrhea - Kanjanopas , Thagoon; Chang, Arunchai; Akarapatima , Keerati; Charoenlap , Cheep; Pakdeejit , Songklod; Rattanasupa , Attapon (Srinagarind Medical Journal, 2022)
Background and Objective: Zollinger-Ellison syndrome (ZES) is an extremely rare condition caused by a neuroendocrine tumor, namely gastrinoma, associated with gastric acid overproduction. The typical presentations include recurrent peptic ulcers accompanied by chronic diarrhea. Method: We present a case report using the information extracted from medical records at Hatyai Hospital. Results: A 55-year-old woman presented with intermittent epigastric pain and chronic diarrhea. Upper endoscopy revealed multiple small gastric polyps accompanied by multiple ulcers in the postbulbar region. Magnetic resonance imaging showed a hypervascular tumor located in the gastrinoma triangle with liver metastasis. The condition was diagnosed as an aggressive gastrinoma based on the histopathology. The patient’s symptoms responded well to supportive treatment. Conclusion: The present case emphasizes the importance of having high clinical suspicion of ZES, especially in patients presenting with peptic ulcer disease and chronic diarrhea, which may help in the early diagnosis of the patient and provide appropriate treatment.